2020
DOI: 10.2147/rmhp.s250930
|View full text |Cite
|
Sign up to set email alerts
|

<p>Knowledge, Attitude, and Practice of Jinka University Students About Yellow Fever, Ethiopia: A Cross-Sectional Study</p>

Abstract: Background Yellow fever (YF) is endemic in South Omo area of Ethiopia. Although Jinka University (JKU) is located in South Omo Zone, there is no information regarding the level of knowledge, attitude, and practice of students toward YF. The current study aimed to assess knowledge, attitude, and practice of JKU students toward YF and factors associated with the overall knowledge and attitude about the disease. Methods In this cross-sectional study, a semi-structured self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 23 publications
(23 reference statements)
6
3
0
Order By: Relevance
“…The fear of being at risk for yellow fever and someone working or living in the forest zones being at higher risk was again mentioned by a majority of the participants. Our findings in these regards were in line with a similar study result reported by (13) in Jinka, Ethiopia and (15) among the general population in South Omo Zone. These positive attitudes of the nomadic population towards yellow fever put them in a position to most likely adopt preventive measures therefore they must be assisted by establishing a system of healthy practices to avoid and curb the spread of the disease sustainably.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The fear of being at risk for yellow fever and someone working or living in the forest zones being at higher risk was again mentioned by a majority of the participants. Our findings in these regards were in line with a similar study result reported by (13) in Jinka, Ethiopia and (15) among the general population in South Omo Zone. These positive attitudes of the nomadic population towards yellow fever put them in a position to most likely adopt preventive measures therefore they must be assisted by establishing a system of healthy practices to avoid and curb the spread of the disease sustainably.…”
Section: Discussionsupporting
confidence: 93%
“…Findings here demonstrated low knowledge on the cause of yellow fever, main transmission vector, breeding point for the transmission vector, and hygienic management of breeding sites. The very low knowledge of these indicators in our study is similar to previous research (13,15). Other studies (15),(19) found very few participants knew that the mosquito is the transmission vector for yellow fever.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…More than three-quarters of travellers were unaware of yellow fever infection and vaccination in India [11]. Other studies highlighted how knowledge was found to be associated with the geographical location of birth and fields of academic study [12], although a community study conducted in Southern Ethiopia found low population knowledge on transmission modes, cause and preventive strategies.…”
Section: Introductionmentioning
confidence: 99%